Rapid, non-invasive characterization of the dispersity of emulsions via microwaves - Yan, Y; Gonzalez-Cortes, S; Yao, B; Slocombe, DR; Porch, A; Cao, F; Xiao, T; Edwards, PP (Royal Society of Chemistry, 2018)
A rapid and non-invasive method to determine the dispersity of emulsions is developed based on the interrelationship between the droplet size distribution and the dielectric properties of emulsions. A range of water-in-oil emulsions with different water contents and droplet size distributions were analysed using a microwave cavity perturbation technique together with dynamic light scattering. The results demonstrate that the dielectric properties, as measured by non-invasive microwave cavity analysis, can be used to characterise the dispersity of emulsions, and is also capable of characterizing heavy oil emulsions. This technique has great potential for industrial applications to examine the sedimentation, creaming and hence the stability of emulsions.